PENERAPAN METODE TUTOR SEBAYA DALAM PEMBELAJARAN TARI DI SMPN 1 UNGGUL BUKITTINGGI - Yorian, Anisa Suyana; Astuti, Fuji; Asriati, Afifah (FBS Universitas Negeri Padang, 2019)
AbstractThis article aims to describe the traditional dance study with method of peer tutors in SMP 1 Superior Bukittinggi. This type of research is research experiments. Test skills (psychomotor) students in learning dance with wiraga indicators, wirama, wirasa, property, floor patterns. Types of data using primary data and secondary data. The technique of data collection is done by way of observation, study and library test appearances. And data were analyzed using t-test paired sample t test (paired t-test). The results showed that there is a difference between learning outcomes students learn the art of dance with the application of peer tutor methods with conventional approaches to learning outcomes. This can be seen from the average value of experimental class learning outcomes i.e. 87,66, while the average value of control class learning outcomes i.e. 84.57. Then strengthened again with the results of hypothesis testing where tcÂount > ttaÂble (9,989 > 2,0021). Then H1 accepted and H0 is rejected.Keywords: Peer tutors, learning methods of danceÂ